2010
DOI: 10.1111/j.1750-3841.2010.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Antimicrobial Activity of Allyl Isothiocyanate during Long‐Term Storage in an Oil‐in‐Water Emulsion

Abstract: This study investigated the stability and antimicrobial activity of allyl isothiocyanate (AITC) in medium chain triglyceride (MCT) or soybean oil (SBO) dispersed in an oil-in-water (o/w) system during long-term storage. Oil type, content, and oxidative stability affect the stability and antimicrobial activity of AITC during storage. High oil content is favorable for AITC stability in the emulsion. Notably, AITC with MCT is more stable than AITC with SBO with the same oil content. Consequently, AITC with MCT is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…LaraLledó, Olaimat, and Holley (2012) also found that the MIC of AITC against L. monocytogenes GLM4 was 75 ppm in BHI broth at 20 C. The MIC increased up to 10 times at 37 C, reaching 100 ppm against all L. monocytogenes strains and 60e100 ppm against Salmonella strains (Table 1). These results agree with previous findings of Liu and Yang (2010) who found that MICs of AITC against Salmonella enterica and L. monocytogenes were 100 and 200 ppm in an oil-in-water emulsion incubated at 37 C, respectively. Kyung and Fleming (1997) found that the MIC of AITC against L. monocytogenes and S. Typhimurium was 200 and 50 ppm, respectively, in Tryptic Soy Broth incubated at 37 C. Palaniappan and Holley (2010) found the MIC of AITC against S. Typhimurium to be 0.31 mM (w31 ppm) in MH broth incubated at 37 C. In contrast, the MBC of AITC was higher at the lower temperature, increasing from 120 to 180 ppm at 37 C to 500e600 ppm at 21 C against Salomonella strains and from 120 to 160 ppm at 37 C to 200e300 ppm at 21 C against L. monocytogenes strains.…”
Section: Mic and Mbc Of Aitc Against Salmonella And L Monocytogenes supporting
confidence: 95%
See 1 more Smart Citation
“…LaraLledó, Olaimat, and Holley (2012) also found that the MIC of AITC against L. monocytogenes GLM4 was 75 ppm in BHI broth at 20 C. The MIC increased up to 10 times at 37 C, reaching 100 ppm against all L. monocytogenes strains and 60e100 ppm against Salmonella strains (Table 1). These results agree with previous findings of Liu and Yang (2010) who found that MICs of AITC against Salmonella enterica and L. monocytogenes were 100 and 200 ppm in an oil-in-water emulsion incubated at 37 C, respectively. Kyung and Fleming (1997) found that the MIC of AITC against L. monocytogenes and S. Typhimurium was 200 and 50 ppm, respectively, in Tryptic Soy Broth incubated at 37 C. Palaniappan and Holley (2010) found the MIC of AITC against S. Typhimurium to be 0.31 mM (w31 ppm) in MH broth incubated at 37 C. In contrast, the MBC of AITC was higher at the lower temperature, increasing from 120 to 180 ppm at 37 C to 500e600 ppm at 21 C against Salomonella strains and from 120 to 160 ppm at 37 C to 200e300 ppm at 21 C against L. monocytogenes strains.…”
Section: Mic and Mbc Of Aitc Against Salmonella And L Monocytogenes supporting
confidence: 95%
“…AITC reduced Salmonella and L. monocytogenes numbers by 2.2 and 4.1 log 10 CFU/ml, respectively, at neutral pH, or by 2.6 and 1.2 log 10 CFU/ml at acidic pH, respectively, after 10 d of incubation at 4 C. The results at higher pH are explained by the instability of AITC since it was not detected after 24 h at pH 9.0 when incubated at any temperature (Table 6). It is believed that AITC is susceptible to attack from nucleophiles such as water, OHÀ, and amino groups (Liu & Yang, 2010). Therefore under alkaline conditions AITC easily decomposed to form new compounds which were less bactericidal (Ohta et al, 1995).…”
Section: Combined Ph and Temperature Effects On In Vitro Aitc Antimicmentioning
confidence: 99%
“…In Gram-negative bacteria, the passage through the outer membrane is regulated by the presence of hydrophilic channels (porins) that usually exclude the entry of hydrophobic compounds such as ITCs. Moreover, the outer membrane of these bacteria lacks phosphoglycerides and, hence, lacks the effective channels for hydrophobic diffusion (Bos et al 2007;Cohen 2011;Liu and Yang 2010). However, the results obtained with the zeta potential measurements are not correlated with the antimicrobial susceptibility tests.…”
Section: Discussionmentioning
confidence: 56%
“…AITC is easily decomposed due to its electrophilic character. This relatively immediate aqueous degradation of AITC is an advantage when considering it as a disinfectant because it will not persist in the environment (Liu and Yang 2010;Mushantaf et al 2012). Moreover, in a study about the safety of AITC for the use as a food additive, the European Food Safety Authority (EFSA) Panel on Food Additives and Nutrient Sources added to Food (ANS) concluded that no significant safety concerns are expected with its use as anti-spoilage agent (EFSA 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is probable that the major chemical species formed by bacterial hydrolysis of sinigrin in the mustard extract was AITC . Since AITC is difficult to measure accurately in aqueous media because it is volatile and easily decomposes to new products under these circumstances (Liu and Yang, 2010), sinigrin degradation was used as a more dependable measure of its formation. Further, it was evident that C. jejuni strains possess myrosinase-like enzyme(s) as has been observed with many other foodborne bacteria (Herzallah et al, 2011) and were able to degrade 87% to 91% (975 to 1020 ppm) of the sinigrin present in buffered MH broth (pH 7.0) by 21 d at 35°C (Table 3).…”
Section: Viability Of C Jejuni On Chicken Breastsmentioning
confidence: 99%